Role of self-efficacy in dealing with patients with alcohol dependence syndrome - Treiadalang Nongtdu; Omesh Kumar Elukapally; Sireesha Srinivas Rao; L.V.R. Usha; Raghuveer Raju Boosa (Telangana Journal of Psychiatry)
Background: Self-efficacy plays a very important role in maintaining abstinence as well as predicting response to treatment in patients with alcohol dependence syndrome. Aims: The aim of the study was to assess and compare the level of self-efficacy among relapsed and abstinent patients with alcohol dependence syndrome. Materials and Methods: A cross-sectional study was conducted on patients with alcohol dependence syndrome recruited from the deaddiction ward of a tertiary care hospital who had relapsed (n = 50) and compared with abstinent (n = 50) on treatment with anticraving agents. All study subjects of both groups were assessed for self-efficacy using the Alcohol Abstinence Self-Efficacy Scale (AASES) – Confidence not to drink and AASES – Temptation to drink subscales. Results: Mean total scores of confidences not to drink subscale of the self-efficacy scale were higher in the abstinence group (43.86) than relapse group (37.24) (P = 0.01). In the temptation to drink subscale, mean total scores were higher for the relapse group (41.08) than the abstinent group (36.7) (P = 0.09). Conclusion: These findings indicate that self-efficacy had a significant effect on abstinence in persons with alcohol dependence syndrome.